A green, reusable and remarkable catalyst for selective aerobic oxidation of alcohols: Construction of Cu(BDC) on the surface of carboxymethyl cellulose fiber. (September 2021) - Javanbakht, Siamak; Mohammadian, Reza; Farhid, Hassan; Shaabani, Ahmad; Amini, Mostafa M.
Graphical abstract: Highlights: Cu(BDC) was successfully constructed on the surface of carboxymethyl cellulose fiber. Cu(BDC)/CMC hybrid was utilized as efficient catalyst for selective aerobic oxidation of alcohols. It could act as an efficient, environmentally benign, and reusable heterogeneous catalyst. Primary aromatic alcohols are easily converted in comparison with secondary aromatic alcohols. Significant result is high conversion without causing any deactivation or poisoning for Cu(BDC). Abstract: Removing or reducing the amount of metal used in catalytic methods is one of the most important concerns of today's activists in the field of green chemistry. In the present paper, copper terephthalate metal-organic framework (MOF) is chemically attached to carboxymethyl cellulose fiber via an in-situ synthesizing method. The synthesized novel hybrid material (Cu(BDC)/CMC) was applied as an efficient, reusable, and environmentally benign heterogeneous catalyst for the aerobic oxidation of alcohols to the corresponding aldehydes and ketones with good yields under mild conditions. FT-IR, XRD, TGA, SEM, EDS, and TEM techniques confirmed successful construction of catalyst. Obtained results revealed that primary aromatic alcohols are easily converted to aromatic aldehydes in high yields (from 70 to 94 %) with the zero-order kinetics model without additional oxidation to carboxylic acids compared to secondary aromatic alcohols (yields: from 6 to 22). The outstanding advantages of the synthesized catalyst are a non‐hazardous catalyst, desired yields, good selectivity, operational simplicity, mild reaction conditions, and reusability. On the other hand, this catalytic system overcomes essential defects of copper terephthalate MOFs as a catalyst, such as poisoning, deactivation, and non-reusability nature.